(untitled) (Journal of Partial Differential Equations, 2025)
This paper is devoted to estimates on weighted L^q-norms of the nonstationary 3D Navier-Stokes flow in an exterior domain. By multiplying the Navier-Stokes equation with a well selected vector field, an integral equation is derived, from which, we establish the weighted estimate ∥|x|^αu(t)∥_q ≤ C(1+t^α2 +ε )t^-32(1-1q) ,t>0, where 0<α≤1 and 320 holds, where α>0 and 1